Research on tuberculosis in Peru: bibliometric analysis 1981-2010 - Yagui-Moscoso, Martín (2012)
Background: Tuberculosis (TB) is sanitary and national research priority. Scientific production on TB in Peru has not been studied. Objectives: To analyze publications on tuberculosis (TB) done in Peru in the period 1981-2010. Design: Bibliometric study on tuberculosis in Peru. Setting: Universidad Nacional Mayor de San Marcos and Instituto Nacional de Salud, Lima, Peru. Analysis unit: Original articles including reports and series of cases completely developed in Peru or multicentre studies with participation of Peruvian settings. Interventions: Bibliographic search was performed in journals with indization in Medline, SciELO and LILACS 1981-2010. Year of publication, authors, time for realization, language, study area, publication type, study design, study field, population studied, type of research as defined by WHO, institutions participating, financing, and impact factor were registered for each article. Main outcome measures: Bibliometric indicators of production. Results: Two hundred and thirty-three articles on tuberculosis were identified. Average time of studies duration was 2.79 ± 3.55 years, and average time between end of study and publication was 2.95±1.65 years. Study areas were 68 (29.2%) mainly clinical, 66 (28.3%) epidemiological, 56 (24%) public health themes. Only 27.9% were published in a national biomedical journal. Most articles had participation of international institutions (71%). Conclusions: In spite of evident increase in scientific production on TB in Peru, it is still far from the production of more developed countries. Along adopting measures to increase scientific production and research of TB as a national sanitary problem, it is necessary to prioritize such investigation by national agenda so it may be more effective.